PERANCANGAN REPOSITORY DIGITAL STIKOM TUNAS BANGSA MENGGUNAKAN CODEIGNITER - Willy Hairis Resmantama Silaen; Saifullah Saifullah; Eka Irawan (STMIK Budi Darma, 2019)
This study aims to design a Codeigniter-Based New Repository. This software serves to simplify the process of designing the repository. This research also aims to facilitate students and the general public to access examples of student thesis at Stikom Tunas Bangsa Pematangsiantar. This research method is Research and Development. The development model used is Waterfall which consists of analysis, design, implementation, and testing. Based on the results of this study, it can be concluded that the results of software development are in the form of Codeigniter-Based Digital Repository.Keywords: Repository, Code igniter.